Metabolic checkpoints in glioblastomas: targets for new therapies and non-invasive detection - Li, Wenhao; Wang, Zhihao; Chen, Siliang; Zuo, Mingrong; Xiang, Yufan; Yuan, Yunbo; He, Yuze; Zhang, Shuxin; Liu, Yanhui (Frontiers in Oncology, 2024)
Glioblastoma (GBM) is a highly malignant tumor of the central nervous system that remains intractable despite advancements in current tumor treatment modalities, including immunotherapy. In recent years, metabolic checkpoints (aberrant metabolic pathways underlying the immunosuppressive tumor microenvironment) have gained attention as promising therapeutic targets and sensitive biomarkers across various cancers. Here, we briefly review the existing understanding of tumor metabolic checkpoints and their implications in the biology and management of GBM. Additionally, we discuss techniques that could evaluate metabolic checkpoints of GBM non-invasively, thereby potentially facilitating neo-adjuvant treatment and dynamic surveillance.